Chiral Lithium Amido Aryl Zincates: Simple and Efficient Chemo‐ and Enantio‐Selective Aryl Transfer Reagents. (17th January 2019) - Chaumont‐Olive, Pauline; Rouen, Mathieu; Barozzino‐Consiglio, Gabriella; Ben Abdeladhim, Amel; Maddaluno, Jacques; Harrison‐Marchand, Anne
Abstract: An enantioselective aryl transfer is promoted using chiral tricoordinated lithium amido aryl zincates that are easily accessible reagents and whose chiral appendage is simply recovered for reuse. The arylation reaction is run in good yields (60 % average on twenty substrates) and high enantiomeric excesses (95 %  ee average). This occurs whatever the ortho, meta, or para substituent borne by the substrate and a complete chemoselectivity is observed with respect to the aldehyde function. Sensitive groups such as nitriles, esters, ketones, and enolisable substrates resist to the action of the ate reagent, warranting a large scope to this methodology.